The occurrence of the Atlantic species Pisodonophis semicinctus (Osteichthyes: Ophichthidae) in the Gulf of Antalya, Turkey - Gökoğlu, Mehmet; BiÃ§er, Erkan; Korun, Jale; Gökoğlu, Kemal; Teker, Serkan (Acta Aquatica: Aquatic Sciences Journal, 2020)
Fishermen caught a different eel species at night with hook on July 7, 2019 (36°48'59.21"N: 30°38'23.44"E). This fish has not been seen before in the Gulf of Antalya. This fish was identified as Pisodonophis semicinctus (Richardson, 1848). With the identification of this fish, a new species was added to the fish fauna of the Gulf of Antalya.  In the present paper, we reported P. semicinctus for the first time from the Gulf of Antalya, Turkey (North-Eastern Mediterranean), for the third time from marine waters of Turkey.Keywords: Occurence; Pisodonophis semicinctus; the Gulf of Antalya